Depletion of Blood-Borne Macrophages Does Not Reduce Demyelination in Mice Infected with a Neurotropic Coronavirus - Xue, Shurong (American Society for Microbiology, 1999)
Mice infected with the neurotropic coronavirus mouse hepatitis virus strain JHM (MHV-JHM) develop a chronic demyelinating disease with symptoms of hindlimb paralysis. Histological examination of the brains and spinal cords of these animals reveals the presence of large numbers of activated macrophages/microglia. In two other experimental models of demyelination, experimental allergic encephalomyelitis and Theiler’s murine encephalomyelitis virus-induced demyelination, depletion of hematogenous macrophages abrogates the demyelinating process. In both of these diseases, early events in the demyelinating process are inhibited by macrophage depletion. From these studies, it was not possible to determine whether infiltrating macrophages were required for late steps in the process, such as myelin removal. In this study, we show that when macrophages are depleted with either unmodified or mannosylated liposomes encapsulating dichloromethylene diphosphate, the amount of demyelination detected in MHV-infected mice is not affected. At a time when these cells were completely depleted from the liver, approximately equivalent numbers of macrophages were present in the spinal cords of control and drug-treated animals. These results suggest that blood-borne macrophages are not required for MHV-induced demyelination and also suggest that other cells, such as perivascular macrophages or microglia, perform the function of these cells in the presence of drug.